Knowledge of Hand Hygiene and Oral Health Students at Methodist 3 Private Primary School Medan - Angelia, Veronica; Sofyanti, Ervina (Talenta Publisher, 2021)
Aims: The aim of this study was to assess the knowledge among students at private school towards hand hygiene and oral health in Medan, Indonesia. Materials and methods: A cross-sectional study was conducted among 498 students aged 6-12 years of Methodist 3 Primary School in Medan, Indonesia. Knowledge was asssed using hand hygiene and oral health questionnare. Results: 86.95% of students (426 out of 490) had good knowledge regarding hand hygiene and 78.4% of students (384 out of 490) had good knowledge regarding oral health. Conclusion: The results of this study indicate that comprehensive hand hygiene and oral health educational programs for primary students are required to achieved this goal.